6 - Race, Class and Voting Patterns in South Africa’s Electoral System: Ten Years of Democracy: by Adam Habib & Sanusha Naidu - Habib, Adam; Naidu, Sanusha (Africa Development, 2006)
In the run up to South Africa’s three national elections both academia and the media advocated that electoral behaviour would be informed by the race census thesis. This article challenges this dominant thesis by using evidence from post- apartheid South Africa’s three general elections which suggests that the racial census thesis is not the only factor that determines and/or explains voter behaviour of the South African electorate. The indications are that significant sections of the electorate make rational choices during elections, and decide on the bases of information available to them that guides them to choose which party most closely represent their material and other interests. Therefore the article concludes that the link between racial/tribal identities and electoral behaviour is not strong enough and that opposition politicians who do not recognise this will continue to make the mistake of basing their electoral campaigns on crude racial assumptions about the South African electorate, resulting in failure to attract the support of a cross-section of the electorate. And the latter is bound to have negative consequences for the consolidation of democracy in the country.